1997
DOI: 10.2307/1131672
|View full text |Cite
|
Sign up to set email alerts
|

The Consistency and Concomitants of Inhibition: Some of the Children, All of the Time

Abstract: Toddlers displaying extremely inhibited behavior may be at risk for becoming socially withdrawn. However, behavioral inhibition may be a multifaceted characteristic, and its concurrent relation to toddler wariness with peers has not been examined. In this study, 108 toddlers (54 females) and their mothers were observed in novel situations involving unfamiliar settings, adults, and peers. Vagal tone, temperament, separation-reunion behavior, and maternal oversolicitousness also were assessed. There was little c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
239
4
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(261 citation statements)
references
References 0 publications
14
239
4
2
Order By: Relevance
“…During the past decade, investigators have consistently reported linkages between maternal control and overprotectiveness and children ' s social withdrawal, anxiety, and shyness (Bayer, Sanson, & Hemphill, 2006 ;McShane & Hastings, 2009 ). For example, Rubin, Hastings, Stewart, Henderson, and Chen ( 1997 ) found that mothers of temperamentally shy toddlers were " oversolicitous, " that is, they were observed to be highly affectionate and shielding of their toddlers when it was neither appropriate nor sensitive to do so.…”
Section: Parenting B Eliefs and B Ehaviorsmentioning
confidence: 99%
“…During the past decade, investigators have consistently reported linkages between maternal control and overprotectiveness and children ' s social withdrawal, anxiety, and shyness (Bayer, Sanson, & Hemphill, 2006 ;McShane & Hastings, 2009 ). For example, Rubin, Hastings, Stewart, Henderson, and Chen ( 1997 ) found that mothers of temperamentally shy toddlers were " oversolicitous, " that is, they were observed to be highly affectionate and shielding of their toddlers when it was neither appropriate nor sensitive to do so.…”
Section: Parenting B Eliefs and B Ehaviorsmentioning
confidence: 99%
“…The paradigm was adapted based on other versions of the paradigm [18][19][20][21][22][23][24][25][26][27][28]. The final paradigm involved two researchers and lasted around 20 min.…”
Section: Observational Paradigmmentioning
confidence: 99%
“…The clown costumes prevented the children from recognizing the researchers. Clowns or puppets have commonly been used in previous adaptations to enhance the unfamiliar nature of the situation [19,22,[25][26][27][28]. During training, researchers viewed a detailed presentation on the construct (BI) and its behavioral signs.…”
Section: Observational Paradigmmentioning
confidence: 99%
See 2 more Smart Citations